2021
DOI: 10.1108/ijchm-09-2020-1079
|View full text |Cite
|
Sign up to set email alerts
|

Green mindfulness and green creativity nexus in hospitality industry: examining the effects of green process engagement and CSR

Abstract: Purpose This study aims to examine the effect of frontline managers’ green mindfulness on their green creativity directly and through green creative process engagement (GCPE). Furthermore, perceived corporate social responsibility (CSR) moderates the link between green mindfulness and GCPE. Design/methodology/approach The data were collected from 592 frontline managers from the hospitality industry of Pakistan. The data were analyzed using Hayes’ PROCESS macro. Findings The findings indicate that green min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 86 publications
5
96
0
Order By: Relevance
“…We expect a positive association between green values and green creativity according to the current literature, which has acknowledged that personal values can influence individual attitudes and behavior ( Al-Ghazali and Afsar, 2021 ; Kalyar et al, 2021 ). Empirical studies ( Andersson et al, 2005 ; Schultz et al, 2005 ) have reported a significant and positive impact of personal environmental values on individual environmentally friendly behavior.…”
Section: Theory and Hypothesesmentioning
confidence: 89%
“…We expect a positive association between green values and green creativity according to the current literature, which has acknowledged that personal values can influence individual attitudes and behavior ( Al-Ghazali and Afsar, 2021 ; Kalyar et al, 2021 ). Empirical studies ( Andersson et al, 2005 ; Schultz et al, 2005 ) have reported a significant and positive impact of personal environmental values on individual environmentally friendly behavior.…”
Section: Theory and Hypothesesmentioning
confidence: 89%
“…Individual mindfulness focuses on the ability to continuously create and use new categories in perception and interpretation of the world [ 28 , 38 ]. Mindfulness captures a quality of consciousness characterized by clarity and vividness of current experience and functioning.…”
Section: Mindfulness Concept In Organizational Behaviormentioning
confidence: 99%
“…The approach of mindfulness identifies the management flexibility values in structuring and timing investment decisions while encountering unclear circumstances, varying the risks of the investment proposal at different stages [ 15 , 24 , 28 ]. Accordingly, the theory of mindfulness is suitable for the application to investigating firms’ environmental management employment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations